Shaka Goichidaiki Zue: Vernacularization and Visualization of Buddha’s Biography in Nineteenth-Century Japan - Wei Xiang (Religions, 2024)
Since the appearance of Buddha, texts and images depicting his life have circulated across Eurasia, serving as significant mediums for disseminating Buddhist ideology. Japan has historically been influenced by the canon of Chinese Buddhism while concurrently striving to promote the indigenization of Buddhism. This endeavor reached its peak during the Edo period, notably exemplified in the Shaka goichidaiki zue, illustrated by the world-renowned artist Hokusai Katsushika. Originating from Buddhist believers, it presents an adaptation based on the socio-historical context of pre-modern Japan, particularly manifesting evident shifts in emphasizing royal authority, the salvation of females, and ethical relationships. Entering the Meiji era, this pre-modern illustrated manuscript underwent repeated printing, playing an important role in the modernization of Buddhism.